Teachers' diagnostic judgments on tasks as information processing – The role of pedagogical content knowledge for task diagnosis. (March 2022) - Rieu, Andreas; Leuders, Timo; Loibl, Katharina
Abstract: When assessing task difficulty, teachers perceive, interpret, and integrate information about relevant features of the task by applying their topic-specific pedagogical content knowledge (PCK). These assumptions on the processes underlying diagnostic judgements on tasks have rarely been modeled and investigated systematically. In an experimental study, we assume two processes (identifying relevant task features and integrating information on multiple features) and predict the influence of PCK and available time on the accuracy of task judgments of 212 student teachers. The results support that PCK is required for both processes and that time pressure only affects the complex process of integrating information. Highlights: Task diagnosis requires knowledge-based information processing. We investigate assumed processes by varying task features in pairwise comparisons. PCK enables the processes of identifying task features and integrating information on multiple features. Time pressure only hampers the complex process of integrating information on multiple task features.